On some extension of optimal control theory - Karamzin, Dmitry Yu [UNESP]; Oliveira, Valeriano A. de [UNESP]; Pereira, F.L.; Silva, Geraldo Nunes [UNESP] (My University, 2014)
Some problems of Calculus of Variations do not have solutions in the class of classic continuous and smooth arcs. This suggests the need of a relaxation or extension of the problem ensuring the existence of a solution in some enlarged class of arcs. This work aims at the development of an extension for a more general optimal control problem with nonlinear control dynamics in which the control function takes values in some closed, but not necessarily bounded, set. To achieve this goal, we exploit the approach of R.V. Gamkrelidze based on the generalized controls, but related to discontinuous arcs. This leads to the notion of generalized impulsive control. The proposed extension links various approaches on the issue of extension found in the literature.
Keywords: Optimal Control; Impulsive controls; maximum principle